Molecular Detection of Gardnerella Vaginalis Isolated from Preterm Labor Patients and Study of Some Factors on Biofilm Formation in Al-Hilla City, Iraq - Ilham A. Bunyan (Journal of Global Pharma Technology, 2018)
Objectives: the present study aims to isolation and identification of G.vaginalis from preterm labor, detection of bio film formation of G.vaginalis and effect of some factor on bacterial adherence. Material and methods: One hundred fifty clinical sample were collected from preterm labor patients with (bacterial vaginosis, urinary tract infection and aborted women) 80, 15, 55 respectively, admitted to Babylon Maternity and pediatric hospital and Al-Hilla Teaching Hospital, at the period from February to October 2016. These high vaginal samples were subjected to different methods of identification of G.vginalis. Results and conclusion: It was found that 6 (4%) G.vaginalis isolates were recovered by using selective media where 30 (20%) isolates were recovered dependent on direct extraction to high vaginal swab on molecular level.  We  were  detection and found  that  (4) isolates were gave strong biofilm While the other Gave moderate then subjected to some factors to reduce , The effect (Alum ,sodium bicarbonate  and sodium chloride)  at concentration (50%) which gave results (100%) very effective to eradication bio film ,the antibacterial activity of  thymol plant extract (carvacrol) at concentration (50%) were investigated the results proved that is effective  on disrupted biofilm in (83.4%). The used of metronidazole were very effective on biofilm (100%)as well as in Alum ,sodium chloride and sodium bicarbonate The results showed that all factors below have the ability to destruction G.vaginalis biofilm .Keywords: G. vaginalis, cpn60, 16sRNA, bio film, Preterm labor.